Allured by Satan, the World and the Flesh: Representations of Temptation in Medieval English Drama - Pınar Taşdelen (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
According to medieval Christian understanding, human beings have three obstacles or adversaries that mankind must overcome to achieve salvation: Satan, the world and the flesh. The Holy Trinity embodied in the Father, the Son and the Holy Ghost is in contrast to Satan, the world and the flesh. The ideas of heaven and hell are developed with regard to the avoidance of temptation, putting emphasis on the possibility of being abstained from temptation. Medieval dramatists represent the temptations in several mystery and morality plays so as to warn their audience against temptation, present temptation as something to be abstained from through biblical accounts, beginning with Satan’s temptation, followed with an individual’s falling into temptation oneself. Accordingly, this article aims to analyse the dramatic representations of the temptations by medieval playwrights with references to specific mystery and morality plays in order to reveal how spiritual and earthly temptation is handled in the plays. Thereby, an individual’s own temptation with/without the possibility of salvation is questioned.